Improving epidural catheter fixation using benzoin tincture with transparent film dressing for postoperative pain control: A randomized controlled trial - Orawan Pongraweewan (2019)
© 2018, Medical Association of Thailand. All rights reserved. Objective: To evaluate the incidences of the peeling-off of transparent dressings and the migration of epidural catheters after the application of benzoin tincture. Materials and Methods: This double-blinded, randomized controlled trial was performed on 552 patients receiving continuous epidural analgesia after abdominal and thoracic surgeries at Siriraj Hospital. Patients were equally allocated into 2 groups. In “Group B”, patients were painted before the placement of dressings with benzoin tincture on the skin and the epidural catheters; the tincture was provided in ready-to-use packs produced by the Division of Pharmacy, Siriraj Hospital. In “Group T”, patients were not painted. Photos were taken upon completion of the dressings, at the finish of operations, and once daily until the dressings were removed. The dressings were assessed by two independent researchers who did not know the patient groups. Results: A total of 523 patients were analyzed. The incidences of the whole sheet peeling off, and the consequential need for redressing as the catheters were no longer secured, were 71 (27.8%) in Group T and 47 (17.5%) in Group B (p = 0.005). This gave the number needed to benefit of 9.7, 95% confidence interval [CI] 5.75 to 31.92; absolute risk reduction 0.10, 95% CI 0.03 to 0.17; relative risk 0.55, 95% CI 0.39 to 0.77; and relative risk reduction 0.4505, 95% CI 0.22-0.6. The overall migration of the catheters was significantly less in the benzoin tincture group. Conclusions: Applying benzoin tincture on the skin and epidural catheters before placing transparent film dressings significantly reduced the incidences of dressing peeling off and migration of the epidural catheter on the second postoperative day.